Measuring the Influence of Social Humanity on Inclusive Community Development Using Correlation and Regression Analysis - Kabila, Kassongo; Kalonji, Mobutu; Mukendi, Banza (Journal Social Humanity Perspective, 2024)
The paper explores how Social Humanity helps to create inclusive communities and makes it a strategic aspect of the study of management. Although the earlier studies have highlighted inclusivity either as a compliance requirement or as an element of corporate social responsibility, the current study redefines inclusivity as a relationship process based on empathy, compassion, and solidarity. Using a quantitative design, data were gathered by way of a structured survey of 300 participants who were sampled purposely and across a wide range of demographics. Social Humanity (Variable X) and Inclusive Communities (Variable Y) constructs have been assessed with validated Likert-scale measures, whereas the results were processed in SPSS 25. The descriptive statistics revealed that the perception of inclusiveness (M = 3.80, SD = 0.90) and support of Social Humanity (M = 4.25, SD = 0.75) was very high in the case of moderate perception. The results of inferential analyses showed significant (r = 0.62, p < 0.001) positive correlation between Social Humanity and Inclusive Communities and regression analyses resulted in the finding that age and socioeconomic status made significant but less significant contributions respectively. The results highlight the importance of understanding that inclusive community development is not maintained through structural processes but has to be purposefully nurtured through cultivating humanity-based practices in organizational and societal structures. The current study will add to the body of management knowledge because it puts Social Humanity in the category of quantifiable strategic capital, and it provides evidence that can be applied in leadership development, policy-making, and organization design. Finally, the practice of Social Humanity improves resilience, innovation and sustainable collective well-being.